(untitled) (Texas Journal of Medical Science, 2021)
Hypertrophy of left ventricle has been recognized as a significant clue for cardiovascular insults in clinical practice. It’s crucial to understand whether left ventricle mass increases with age. This crosssectional study included 100 healthy males in total. All of the participants were assigned to one of four groups: Group I (N = 36) consisted of people aged 20 to 29, Group II (N = 28) of people aged 30 to 39, Group III (N = 19) of people aged 40 to 49, and Group IV (N = 17) of people aged 50 to 60.The Devereux method is used to make measurements of the left ventricle at end-diastole by M-mode derived echocardiography, as recommended by the American Society of Echocardiography (ASE). With age, LVM, LVMI, and RWT all increased statistically significantly. The measures of LVM and LVMI were statistically significant in groups I-III and I-IV. RWT varied significantly between groups I-II, I-III, and I-IV, as well as between groups II and III. IVSTd and PWTd showed a substantial increase with age, however LVIDD showed no significant change with age. Groups IV and III had significantly higher IVSTd and PWTd than Group I (p 0.05). Finally, the LV mass increased significantly as the patient’s age increased